Effect of using the six-dimensional strategy The (PDEODE) in the achievement of the second grade students for the scientific concepts and retain them (Journal of the College of Basic Education, 2022)
The main aim of this study is to learn about the effect of the using the six-dimensional strategy (PDEODE) in the achievement of the second grade students for the scientific concepts and retain them. , the researchers used the experimental approach, The sample of theStudy included (70) students of the ( Samaraa) primary school students as (35) students for the experimental group which studied according to the six-dimensional strategy (PDEODE), and (35) students for the control group they wear studied according to the usual method, the test were prepared and it consisted of (10) items as multi-choice type, and the reliability estimate was (0.82). There was statistically significant difference on scientific concepts test for the experimental group. The study recommended several recommendations, including the need to adopting new teaching strategies